Qurʼān kī cār bunyādī iṣ̤tilāḥeṉ : ilāh, rabb, ʻibādat, dīn - Maudoodi, Syed Abul ʻAla, 1903-1979 (Ma̤tbūʻāt-i ishāʻat-i Islām Ṭrasṭ (Series) ;, 1981)
Interpretation of (ilah), (rabb), (ibādat), and (din) expressions frequently used in the Koran.